The wise man's fear - Rothfuss, Patrick, 1973- (Rothfuss, Patrick, 1973- Kingkiller chronicle, 2008)
Kvothe takes his first steps on the path of the hero as he attempts to uncover the truth about the mysterious Amyr, the Chandrian, and the death of his parents. Along the way, Kvothe is put on trial by the legendary Adem mercenaries, forced to reclaim the honor of the Edema Ruh, and travels into the Fae realm where he meets Felurian, the faerie woman no man can resist.